Neuroprotective mechanisms of valproic acid and alpha-lipoic acid in ALS: a network pharmacology-based investigation - Zhang, Dongmei; Han, Ling; Zhang, Wenmo; Wang, Di; Huo, Di; Tan, Xingli; Su, Xiaoli; Wang, Ming; Xu, Jing; Cheng, Jiling; Wang, Jing; Feng, Honglin (Frontiers in Pharmacology, 2025)
IntroductionAmyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disorder, and its multi-mechanism pathology makes single-target therapy insufficient. Valproic acid (VPA) and alpha-lipoic acid (ALA) are known neuroprotective agents, but their combined therapeutic potential and mechanisms in ALS remain unclear.MethodsIn this study, network pharmacology method was used to integrate the target data of VPA, ALA and ALS, and key targets and pathways were screened by function enrichment, protein–protein interaction (PPI), network analysis and molecular docking. Furthermore, Mendel randomization (MR) was used to analyze the causal relationship between targets and ALS risk. The synergistic neuroprotective effects of VPA and ALA were then validated in the hSOD1G93A ALS cell and mouse models.ResultsIn this study, four core targets-TNF, EGFR, MAPK1 and MAPK8-were identified for the first time. Genetic analysis indicated that higher TNF levels and reduced MAPK8 expression are linked to a greater risk of ALS. Molecular docking demonstrated strong binding affinities of both compounds to these targets. In vitro and in vivo experiments showed that the combined therapy significantly improved neuronal survival and motor function, inhibited inflammation and apoptosis by activating the PI3K/AKT/FoxO3a pathway, and yielded significantly better therapeutic effects compared to the single drug treatments.DiscussionVPA and ALA synergistically alleviate ALS by modulating multiple targets and activating the PI3K/AKT/FoxO3a pathway. These findings support their potential as a combinatorial therapeutic strategy for ALS.